Role of Neural Plasticity of Motor Cortex in Gliomas Evaluated by Brain Imaging and Mapping Techniques in Pre- and Postoperative Period: A Systematic Review - Silva, Rhuann Pontes dos Santos; Monteiro, Lucas Nascimento; Dias, Lavinia da Silva; Haddad, Julia Oliveira Dabien; souza, Vitor Bidu de; Oliveira, Vinicius Faustino Lima de; Fernandes, Anna Sabrinny; Olivera, Matheus Fernandes de; Rotta, Jose Marcus (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Resection of infiltrative neuroepithelial primary brain tumors, such as low-grade gliomas (LGGs) remains a neurosurgical challenge. Usual lack of clinical deficit despite LGGs growing in eloquent brain areas may be explained by reshaping and reorganization of functional networks. The development of modern diagnostic imaging techniques could disclose better understanding of the rearrangement of the brain cortex; however, mechanisms underlying such compensation and how it occurs in the motor cortex remain unclear. This systematic review aims to analyze the neuroplasticity of motor cortex in patients with LGGs, as determined by neuroimaging and functional techniques.Methods Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, medical subject headings (MeSH) and the following terms related to neuroimaging, LGGs and neuroplasticity were used with the Boolean operators AND and OR to synonymous terms in the PubMed database. Among the 118 results, 19 studies were included in the systematic review.Results Motor function in patients with LGG was characterized by a compensation in the contralateral and supplementary motor areas and premotor functional networks. Furthermore, ipsilateral activation in these types of gliomas was rarely described. Moreover, some studies did not reveal statistical significance in association between functional reorganization and the postoperative period, which can be explained by the low number of patients.Conclusion Our findings suggest a high pattern of reorganization per different eloquent motor areas and gliomas diagnosis. Understanding this process is useful to guide safe surgical resection and to develop protocols that assess the plasticity, even though functional network rearrangement needs to be better characterized by more studies.
Keywords: plasticity; neurosurgery; gliomas; rehabilitation